EMERGING DISPLAY TECHNOLOGIES IN CONTEMPORARY ART: A TECHNICAL ANALYSIS - Muralidhar Manohar Shenoy (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article examines the transformative role of digital displays in contemporary art and creative expression, investigating the intersection of technology, artistic innovation, and audience engagement. The article analyzes how modern display technologies such as micro-LED have revolutionized artistic creation, presentation, and interaction across multiple platforms, from traditional galleries to immersive digital installations, with particular emphasis on groundbreaking implementations like the MSG Sphere in Las Vegas—a technological marvel featuring the world's largest LED screen with 1.2 million LED pucks across a 580,000-square-foot exosphere display surface. The article encompasses analysis of various display applications in art, including large-format LED installations, interactive digital canvases, and AI-driven artistic collaborations. The article demonstrates that digital displays have fundamentally altered artistic creation and consumption, enabling new forms of expression through data visualization, human-machine collaboration, and immersive experiences. Through examination of both cutting-edge achievements and implementation challenges, the article reveals how display technologies have democratized art access while creating new opportunities for artist-audience interaction through social media and digital platforms, setting new standards for large-scale digital art installations and future technological integration in artistic expression.